1993
DOI: 10.2134/agronj1993.00021962008500040027x
|View full text |Cite
|
Sign up to set email alerts
|

Deriving Fertilizer Recommendations with a Flexible Functional Form

Abstract: General fertilizer response models are useful to derive robust rec· ommendations for farmers who face different circumstances. This pap,er shows that a flexible functional form such as the transcendental cun be applied to develop both agronomically and economically sound n~ommendation tables using a set of soil test, climate, and management variables. Data from thirty-eight experiments on wh1:at response to N and P in the Humid Pampa, Argentina, were used to build a general response model that incorporates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 3 publications
0
6
0
2
Order By: Relevance
“…Field experiments showed a positive effect of soya bean as a previous crop of wheat in relation to corn or other summer crops in the Rolling Pampa, but this effect may be compensated by small rates (5–10 kg N ha −1 ) of fertilizer (Sain and Jauregui 1993). This supports the hypothesis that soya bean may generate an N credit for wheat.…”
Section: Discussionmentioning
confidence: 99%
“…Field experiments showed a positive effect of soya bean as a previous crop of wheat in relation to corn or other summer crops in the Rolling Pampa, but this effect may be compensated by small rates (5–10 kg N ha −1 ) of fertilizer (Sain and Jauregui 1993). This supports the hypothesis that soya bean may generate an N credit for wheat.…”
Section: Discussionmentioning
confidence: 99%
“…Parameter estimation in N response models is generally based on ordinary least squares (e.g., Mombiela et al, 1981; Sain and Jauregui, 1993). This method is easily implemented.…”
mentioning
confidence: 99%
“…To select a particular model for practical use, it is necessary to define criteria for evaluating the different possible models. In numerous studies, response models are evaluated by calculating R 2 values (Anderson and Nelson, 1975; Cerrato and Blackmer, 1990; Sain and Jauregui, 1993). Another approach is to study graphically the distribution of the model residuals (Cerrato and Blackmer, 1990; Bullock and Bullock, 1994).…”
mentioning
confidence: 99%
“…In fact, it is often observed that several models give similarly good fits to the data. Some authors have pro-posed models that relate response to measurable plot characteristics, such as the preceding crop or soil mineral N before fertilizer application (Smith et a!., 1987;Sain and Jauregui, 1993). Much less work has been done on modeling grain protein content or residual mineral N at harvest (Jauregui and Paris, 1985;Fowler eta!., 1989).…”
mentioning
confidence: 99%